2018
DOI: 10.24176/re.v8i2.2358
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Peranan Ekosistem Pendidikan Dalam Penguatan Pendidikan Karakter Peserta Didik

Abstract: Akhir-akhir ini kita sering melihat beberapa aksi kenakalan yang dilakukan oleh peserta didik. Bermacam-macam bentuk kenakalan peserta didik semakin mewarnai kehidupan saat ini, membuat orang tua, guru, tokoh masyarakat dan bahkan Pemerintah resah. Sebagai salah satu alternatif solusi permasalahan, pemerintah menetapkan kebijakan penguatan pendidikan karakter bagi seluruh masyarakat, termasuk bidang pendidikan. Mengingat pentingnya penguatan pendidikan karakter, sangat menarik untuk mendalami bagaimana impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
29

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 1 publication
1
11
0
29
Order By: Relevance
“…In addition to the mass media, community leaders, education observers, and social observers talked about national culture and character issues in various seminars at the local, national and international forums (Rofiani, 2018). Alternative solutions to the character crisis of the Indonesian people were proposed, among others in the form of legislation and strengthening of law enforcement (Perdana, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the mass media, community leaders, education observers, and social observers talked about national culture and character issues in various seminars at the local, national and international forums (Rofiani, 2018). Alternative solutions to the character crisis of the Indonesian people were proposed, among others in the form of legislation and strengthening of law enforcement (Perdana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the implementation of character value appeared in investing character values at school, active participation in school adiwiyata (school program to preserve environment), training in schools by inviting experts, and so on. With the synergy in strengthening character education in schools, it will create a conducive atmosphere in the school environment (Perdana, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Schools need to choose the right strategy to shape these characters through learning processes such as local content of environmental education, and school culture such as routine cleaning of the school environment, exemplary principals and teachers. Perdana (2018) added that a school culture that supports the formation of student character needs to be supported by collaboration between school principals, teachers, parents and the community. This collaboration can produce conducive conditions to support character education.…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai penelitian sebelumnya telah mengkaji tentang bagaimana strategi dalam penguatan pendidikan karakter di satuan pendidikan, seperti penguatan pendidikan karakter dapat berbasis kearifan lokal (Rachmadyanti, 2017;Ramdani, 2018), dengan strategi anak belajar secara full day school (Siregar, 2017), dengan memaksimalkan peranan ekosistem pendidikan (Perdana, 2018), dan juga memaksimalkan peran orang tua (Wulandari & Kristiawan, 2017). Bertolak dari keadaan tersebut, peneliti terdorong untuk melakukan penelitian di SD Negeri 02 Sungai Landia tentang Implementasi penguatan Pendidikan Karakter di Satuan Pendidikan Sekolah Dasar.…”
unclassified